Multi-object near-infrared H alpha spectroscopy of z similar to 1 star-forming galaxies in the Hubble Deep Field North - Doherty, M; Bunker, A; Sharp, R; Dalton, G; Parry, I; Lewis, I; MacDonald, E; Wolf, C; Hippelein, H (2004)
We present preliminary results from a programme to obtain multi-object near-infrared spectroscopy of galaxies at redshifts 0.7 < z < 1.5. We are using the instrument CIRPASS (the Cambridge Infra-Red PAnoramic Survey Spectrograph), in multi-object mode, to survey Hα in galaxies at z ∼ 1. We aim to address the true star formation history of the Universe at this epoch: potentially the peak period of star formation activity. Hα is the same star formation measure used at low redshift, and hence we can trace star formation without the systematic uncertainties of using different calibrators in different redshift bins, or the extreme dust extinction in the rest-ultraviolet (rest-UV). CIRPASS has been successfully demonstrated in multi-object mode on the Anglo-Australian Telescope (AAT) and the William Herschel Telescope (WHT). Here we present preliminary results from one of our fields, the Hubble Deep Field North, observed with the WHT. With 150 fibres deployed over an unvignetted field of ∼15 arcmin, we have several detections of Hα from star-forming galaxies at 0.8 < z < 1.0 and present spectra of the seven brightest of these. By pre-selecting galaxies with redshifts such that Hα will appear between the OH sky lines, we can detect star formation rates of 5 h-270 M⊙ yr-1 (5 δ in 3 hours, ΩM = 0.3, ΩΛ = 0.7). It appears that star formation rates inferred from Ha are, on average, a factor of more than two higher than those based on the UV continuum alone.